1981
DOI: 10.1677/joe.0.0900421
|View full text |Cite
|
Sign up to set email alerts
|

Androgen and Oestrogen Binding in Cytosols of Human Ovarian Tumours

Abstract: The specific retention of androgens and oestrogens by cytoplasmic components of human ovarian tumours was investigated. High-affinity, low-capacity binding of androgens was observed in 88% of tumour specimens and oestrogen binding in 32%. Retention of oestrogens did not occur in the absence of androgen binding. The androgen-binding component, of sedimentation coefficient 7.5-8.5S, showed specificity for 5 alpha-dihydrotestosterone and 17 beta-hydroxy-17 alpha-methyl-estra-4,9,11-trien-3-one (R1881). In some in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

1982
1982
2010
2010

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Expression of the androgen receptor (AR) has been demonstrated in ovarian cancers using ligand binding assays (Hamilton et al, 1981). Further studies have shown AR to be expressed by as many as 90% of epithelial ovarian cancers (Kuhnel et al, 1987).…”
mentioning
confidence: 99%
“…Expression of the androgen receptor (AR) has been demonstrated in ovarian cancers using ligand binding assays (Hamilton et al, 1981). Further studies have shown AR to be expressed by as many as 90% of epithelial ovarian cancers (Kuhnel et al, 1987).…”
mentioning
confidence: 99%
“…The presence in ovarian cancer cells of receptors for oestrogen and progesterone (Holt et al, 1979;Rowland et al, 1985;Sutton et al, 1986), and for androgens (Hamilton et al, 1981), combined with the ability of these cells to synthesise steroid hormones (Heinonen et al, 1982;Backstrom et al, 1983), suggests that hormonal manoeuvres may be useful in the treatment of this condition.…”
mentioning
confidence: 99%
“…Many studies have suggested that estradiol-17ß [1], progesterone [1,2], testosterone and dihydrotestosterone [3] regulate normal ovarian function, and the presence of the cor- Misao/Iwagaki/Sun/Fujimoto/Tamaya responding estrogen, progesterone and androgen receptors has been demonstrated in human normal ovary and in benign and malignant ovarian tumors [4][5][6][7][8]. The growth of some ovarian cancers regresses with tamoxifen [9][10][11], megestrol acetate [9], and medroxyprogesterone acetate treatment [12].…”
Section: Introductionmentioning
confidence: 99%